Age-Related Effects of Stimulus Type and Congruency on Inattentional Blindness - Liu, Han-Hui (Frontiers in Psychology, 2018)
Abstract Background: Most of the previous inattentional blindness (IB) studies focused on the factors that contributed to the detection of unattended stimuli. The age-related changes on IB have rarely been investigated across all age groups. In the current study, by using the dual-task inattentional blindness paradigm, we aimed to explore the age-related effects of attended stimuli type and congruency between attended and unattended stimuli on IB. Methods: The current study recruited 111 participants (30 adolescents, 48 young adults, and 33 middle-aged adults) in the baseline recognition experiments and 341 participants (135 adolescents, 135 young adults, and 71 middle-aged adults) in the inattentional blindness experiment. We applied the superimposed picture and word streams experimental paradigm to explore the age-related effects of attended stimuli type and congruency between attended and unattended stimuli on IB. An ANOVA was performed to analyze the results. Results: Participants across all age groups presented significantly lower recognition scores for both pictures and words in comparison with baseline recognition. Participants presented decreased recognition for unattended pictures or words from adolescents to young adults and middle-aged adults. When the pictures and words are congruent, all the participants showed significantly higher recognition scores for unattended stimuli in comparison with incongruent condition. Adolescents and young adults did not show recognition differences when primary tasks were attending pictures or words. Conclusion: The current findings showed that all participants presented better recognition scores for attended stimuli in comparison with unattended stimuli, and the recognition scores decreased from the adolescents to young and middle-aged adults. The findings partly supported the attention capacity models of inattentional blindness. Key words: attention, inattentional blindness, adolescents, young adults, middle-aged adults